PROLOGUE AND EPILOGUE NARRATIONS OF 'MATA NAJWA: PARA PEMBURU RENTE' - Ikke Dewi Pratama (Leksema: Jurnal Bahasa dan Sastra, 2016)
The study of stylistics has grown wider in literatures and in linguistics. Stylistics provides linguistic features that support the interpretation of certain text so that the investigation becomes comprehensive. This research aims at finding stylistic features of the narrations of the prologue and epilogue of Mata Najwa talk show in an episode entitled Pejabat Pemburu Rente. Using ear-catching word arrangements, the prologue and epilogue successfully attract the audiences’ attention and, thus, the talk show becomes one of the most popular TV show in Indonesia. The stylistic features observed in this research are based on deviation and parallelism. This is a descriptive qualitative research. The data source is Mata Najwa show with the sub-title Pejabat Pemburu Rente, while the data are the prologue and the epilogue of the show. The analysis shows three features in the prologue as well as in the epilogue: figurative language, sound repetition and word repetition.